Development of an assistant program for CAD-to-cosRMC modelling - Du, Hua; Luo, Yue-Tong; Han, Chengcun; Lu, Lei; Yan, Yiman; Sun, Yeshuai; Chen, Yixue; Liu, Songlin (Fusion engineering and design, 2020)
•A visual modeling platform was developed for cosRMC based on OCC and FreeCAD framework.•The reliability of the conversion algorithm has been validated.•A few improvements were made to deal with some extreme CAD models. cosRMC is a three dimensional neutron photon transport Monte Carlo code based on the stochastic statistical method of neutral particle transport. At present, the cosRMC geometry model is imported by writing the input file manually, which leads to time-consuming, inefficient and error-prone problems. This will limit application of cosRMC in fusion neutronics calculations because of the complex geometry in fusion devices. Therefore, in order to improve the modeling efficiency and meet the requirements of calculation and analysis of advanced nuclear facilities, a visual modeling platform, cosVMPT—Visual Modeling Platform for Particle Transport, is developed based on Open Cascade (OCC) as CAD geometry engine and FreeCAD framework as graphical user interface. This platform can realize the complete process from modeling to calculation, then to visualization. In this article, the conversion algorithm from CAD models to cosRMC geometry models is introduced in detail. The reliability of the conversion algorithm is preliminarily verified with some representative models by comparing volumes change before and after conversion. The result shows that the geometries after conversion are in good consistency with the original geometries.